If the jacket fits: A metaphor for teacher professional learning and development. (April 2016) - Tait-McCutcheon, Sandi; Drake, Michael
Abstract: The purpose of this research project was to assist lead teachers to define, analyse, and refine their relationship with professional learning and development through the metaphor of a jacket. Metaphor analysis was used to study 18 lead teachers' from six New Zealand schools co-constructed written metaphors. One major finding was the significant number of metaphors that conceptualised a disadvantageous relationship between teachers and their professional learning and development. An implication of that finding is the need to make explicit and address possible negative dispositions teachers may hold toward their professional learning and development. Highlights: Jackets are proposed as way one to conceptualise professional development. Eighteen lead teachers co-constructed 11 metaphors for professional development. Ten metaphors denoted connections between teachers and PD that could disadvantageous. Co-construction, positioning, humour and time assisted the metaphor development. The metaphors assisted lead teacher to conceptualise their relationship with PD.